Agroforestry-Based Ecosystem Services - Noordwijk, M. van (MDPI, 2021)
Agroforestry, land use at the agriculture-forestry interface that implies the presence of trees on farms and/or farmers in forests, has a history that may be as old as agriculture, but as an overarching label and topic of formal scientific analysis, it is in its fifth decade. The trees as such, and the agroforestry system they are part of, provide direct benefits to the farmer (land manager), often through a combination of marketable goods, subsistence needs of the farm household, buffering climate variability, and protecting soil and water resources. However, it also provides benefits to those sharing the same landscape, the same watershed, biome, or even planet Earth, the latter especially as part of the global climate and biodiversity conservation discourses. These external benefits are generally discussed under the heading ‘ecosystem services’, and are the topic of the collection of papers in this Special Issue.